Motives for pornography use and women's sexual wellbeing: Insights from a 42-country study - Gewirtz-Meydan, Ateret; Feder, Hagit; Nagy, Léna; Koós, Mónika; Kraus, Shane W; Demetrovics, Zsolt; Potenza, Marc N; Ballester-Arnal, Rafael; Batthyány, Dominik; Bergeron, Sophie; Billieux, Joël; Briken, Peer; et al. (Journal of behavioral addictions, 2025)
BACKGROUND AND AIMS: Despite a growing body of research on pornography use among women, there is a lack of understanding of the problematic versus non-problematic nature. The current study aimed to investigate the relationship between women's motivations for pornography use and sexual wellbeing using a cross-sectional, self-report survey design among participants from 42 countries. METHODS: The total sample included 82,243 participants, of whom 46,874 (57.0%) identified as women and were analyzed. The participants' age averaged at M = 29.67 years, with a standard deviation of SD = 10.11. Participants were asked to complete a questionnaire assessing their motivations for pornography use, as well as measures of sexual functioning, sexual desire, and sexual satisfaction. RESULTS: Study results suggest that across cultures, women's motivations for pornography use are associated with their sexual wellbeing. Specifically, when women reported using pornography for their own pleasure or sexual curiosity, it was associated with fewer sexual functioning problems and higher sexual desire. Conversely, when women reported using pornography due to a lack of sexual satisfaction in their relationships, it was associated with more sexual functioning problems. DISCUSSION AND CONCLUSIONS: These findings highlight the need to consider the multifaceted nature of pornography use among women, including the usage motives, to fully understand associations with sexual wellbeing. Additionally, the study emphasizes the importance of conducting further research utilizing longitudinal designs, to establish the directionality between pornography use motivations and sexual wellbeing among women.
Keywords: libido; Motivation; Adolescent; motivations; osobní uspokojení; Female; Personal Satisfaction; mladý dospělý; pornography; Middle Aged; Young Adult; průřezové studie; women; sexual wellbeing; ženské pohlaví; Adult; sexuální chování; mladiství; Libido; dospělí; Cross-Sectional Studies; Sexual Behavior; lidé středního věku; Erotica; motivace; erotika; lidé; Humans; cultural differences